2022
DOI: 10.1038/s41467-022-28466-7
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional excited-state dynamics in the concerted benzyl (C7H7) radical self-reaction to anthracene (C14H10)

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are prevalent in deep space and on Earth as products in combustion processes bearing direct relevance to energy efficiency and environmental remediation. Reactions between hydrocarbon radicals in particular have been invoked as critical molecular mass growth processes toward cyclization leading to these PAHs. However, the mechanism of the formation of PAHs through radical – radical reactions are largely elusive. Here, we report on a combined computational and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The onset of the ion counts at 7.40 ± 0.05 eV correlates nicely with the NIST-evaluated adiabatic ionization energy (IE) of anthracene ( p2 ) of 7.439 ± 0.006 eV (Figure a–d). Additional ion counts from phenanthrene ( p1 ), which has an adiabatic ionization energy (IE) of 7.891 ± 0.001 eV, are also critical; nevertheless, ion counts from phenanthrene (C 14 H 10 , p1 ) and anthracene (C 14 H 10 , p2 ) alone cannot replicate the experimental PIE curve. This discrepancy can be resolved by including a third isomer: benzofulvalene (C 14 H 10 , p3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of the ion counts at 7.40 ± 0.05 eV correlates nicely with the NIST-evaluated adiabatic ionization energy (IE) of anthracene ( p2 ) of 7.439 ± 0.006 eV (Figure a–d). Additional ion counts from phenanthrene ( p1 ), which has an adiabatic ionization energy (IE) of 7.891 ± 0.001 eV, are also critical; nevertheless, ion counts from phenanthrene (C 14 H 10 , p1 ) and anthracene (C 14 H 10 , p2 ) alone cannot replicate the experimental PIE curve. This discrepancy can be resolved by including a third isomer: benzofulvalene (C 14 H 10 , p3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Validated through electronic structure calculations, discrete spiroaromatic hydrocarbon radical transients1a′,6a′-dihydro-5′ H -spiro­[cyclopentane-1,1′-cyclopropa­[ a ]­indene]-2,4-dienyl ( i3 ), 4a′ H -spiro­[cyclopentane-1,2′-naphthalene]-2,4-dienyl ( i4 ), 9b,9c-dihydro-3 H -cyclopentadiene­[2,3]­cyclopropa­[1,2- a ]­naphthalenyl ( i5 ), spiro­[bicyclo[3.1.0]­hexane-6,2′-inden]-2-enyl ( i12 ), and spiro­[cyclohexane-1,2′-indene]-2,5-dienyl ( i13 ) (C 14 H 11 • )prepared through carbon–carbon coupling of the five-membered rings from the doublet radical reactants were revealed to be essential in the gas-phase preparation of phenanthrene (C 14 H 10 , p1 ) and anthracene (C 14 H 10 , p2 ). Cemented through the isomer-selective identification of phenanthrene (C 14 H 10 , p1 ), anthracene (C 14 H 10 , p2 ), and benzofulvalene (C 14 H 10 , p3 ) in a molecular beam via fragment-free, soft photoionization by tunable synchrotron vacuum ultraviolet (VUV) light coupled with a reflectron time-of-flight mass spectrometer (Re-TOF-MS; Supporting Information), these findings afford persuasive testimony on a hitherto elusive class of aromatic, reactive intermediates involved in molecular mass growth processes of aromatics in our universe: spiroaromatics.…”
Section: Introductionmentioning
confidence: 99%
“…Colket and Seery 68 demonstrated that benzyl self-reactions can lead to the formation of PAHs, such as anthracene, phenanthrene, fluorene, acenaphthylene, and pyrene. The mechanism for the production of phenanthrene was later investigated by Hirsch et al, 77 and mechanisms for the production of phenanthrene and anthracene were studied by Kaiser et al 78 In low-pressure pyrolysis experiments, Buckingham et al 64 demonstrated that benzyl loses a hydrogen atom and rearranges to form fulvenallene (C 7 H 6 ). Sivaramakrishnan et al 63 performed shock tube measurements on isotopically labeled benzyl and came to a similar conclusion.…”
Section: Vinylcyclopentadienylmentioning
confidence: 99%
“…Colket and Seery demonstrated that benzyl self-reactions can lead to the formation of PAHs, such as anthracene, phenanthrene, fluorene, acenaphthylene, and pyrene. The mechanism for the production of phenanthrene was later investigated by Hirsch et al, and mechanisms for the production of phenanthrene and anthracene were studied by Kaiser et al…”
Section: Introductionmentioning
confidence: 99%
“…11 This method is able to record the intensity of species, not only as a function of the mass-to-charge ratio (mass spectrum), but also as a function of photon energy (photoionization efficiency (PIE) spectrum), providing impressive isomer-specific measurement capability. 7,12 In recent decades, the application of SVUV-PIMS method has promoted the development of various fields including reaction kinetics, combustion chemistry, [13][14][15] catalysis, 16,17 aerosol chemistry, 18 planetary and interstellar chemistry, [19][20][21] etc.…”
Section: Introductionmentioning
confidence: 99%